The effect of ASI (Acceleration Severity Index) to different crash velocities - Rahmad P, Nasution; Rakhmad Arief, Siregar; Khairul, Fuad; Abdul Hamid, Adom (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.